Risk Sharing and Internal Migration - De Weerdt, Joachim; Hirvonen, Kalle (World Bank, Washington, DC, 2013)
Over the past two decades, more than half the population in rural Tanzania migrated within the country, profoundly changing the nature of traditional institutions such as informal risk sharing. Mass internal migration has created geographically disperse networks, on which the authors collected detailed panel data. By quantifying how shocks and consumption co-vary across linked households, they show how migrants unilaterally insure their extended family members at home. This finding contradicts risk-sharing models based on reciprocity, but is consistent with assistance driven by social norms. Migrants sacrifice 3 to 7 percent of their very substantial consumption growth to provide this insurance, which seems too trivial to have any stifling effect on their growth through migration.